Drafting of two passive swimmer scale models for open-water races - Bolon, B.; Pretot, C.; Clanet, C.; Larrarte, F.; Carmigniani, R. (Physical Review Fluids, 2023)
The interaction between two passive human swimmer scale models is investigated both experimentally and numerically. The Froude number, comparing the swimming velocity to the characteristic wave velocity, is conserved in the study. The interaction is quantified for a large range of relative positions and for three speeds corresponding to cruising, average, and sprint swimming. The associated computational fluid dynamics study using OpenFoam allows us to determine the relative positions that optimize the drafting during an open-water race: just behind a lead swimmer or at the level of the hip of a neighbor, with reductions of drag of 40% and 30%, respectively.